THE IMPACT OF PARENTAL DIVORCE ON THE BEHAVIOR OF ADOLESCENT DRUG ABUSERS - Asra, Muhamad; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The rise of cases of drug abuse and illicit trafficking in the millennial era is very closely related to the development of technological advances and communication in society. There is an increase in drug cases which are increasing not limited to one group or circle, but reaching all circles. In the scope of youth many have been exposed to the effects of these drugs. Whether it's abuse or has entered the realm of illicit circulation, one of the factors is the family itself, namely the existence of a divorce between the parents (broken home) and the lack of support from other family members so that it influences the behavior of the teenager towards negative things. This study aimed to determine the relationship between increased drug abuse and the impact of parental divorce. This study used a systematic review method using database searches from Google Scholar, Scopus, Science direct, PubMed, and Researchgate. This study uses search keywords "Divorce, parents, abusers and drugs". The results of an analysis of 5 national journals illustrate that there is a very close relationship between the impact of parental divorce on the behavior of adolescent drug abusers. There is a significant relationship between the impact of parental divorce and the behavior of adolescent drug abusers. Therefore, it is necessary to carry out correct and appropriate efforts to prevent and eradicate drugs by the government and related stakeholders. Keywords: divorce parents, abusers, drug